(untitled) (Medical Forum Monthly, 2021)
Objective: To observe the correlation between age, follicle count, ovarian volume and fertility according to BMI. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at Radiology Department DHQ Teaching Hospital D.I.Khan for 10 months from March 2013 to December 2013. Materials and Methods: This comparative, cross-sectional study was conducted in the Department of Anatomy, Gomal Medical College, D.I.Khan, Pakistan from March 2013 to December 2013. Sample Size was 100 women selected by consecutive non probability sampling technique. Sample size was calculated using online calculator Raosoft. Inclusion criteria were women aged 18-50 years, married, fertile and infertile. Color Doppler sonoscape with multi frequency transvaginal probes were used in measurements on any day in the start of menstrual cycle by the same observer. The volume was calculated by applying formula for ellipsoid called Prolate ellipsoid formula. The total volume was represented by sum of volume of two ovaries. Data collection site was out patient department of Radiology DHQ Teaching Hospital, D.I.Khan. Demographic variable were age groups, height, weight and presence of fertility. Research variables were ovarian volume and follicle count. Mean and standard deviation were calculated for ovarian volume and follicle count whereas frequency and percentages were calculated for age groups, BMI and presence of fertility. Descriptive statistics along with estimation of parameter was done at 95% confidence interval for proportion and mean. Student- t test was used for significance of difference in ovarian volume between fertile and infertile women with p value <0.05 considered significant. SPSS was used for data analysis. Results: The correlation between age, BMI and fertility parameters (ovarian volume and follicle count) was non-significant (0.105) in fertile females whereas highly significant negative correlation (-0.75) was observed between age and antral follicle counts in infertile females. Conclusion: Ovarian reserve is directly affected by age and weight of females specially among fertile women.